Evaluasi Kinerja Jalur Ganda Kereta Api Solobalapan - Yogyakarta - Hanafi Isnanta Prabawa; Woro Partini Maryunani; Evi Puspitasari (Institut Transportasi dan Logistik Trisakti, 2021)
Solobalapan-Yogyakarta railway track serve up to 100 trains each day that get near to maximum lane capacity on one section of that line. Evaluation consisted of reliability, availability, maintainability and safety criteria. Ministry of Transportation issued Rencana Induk Perkeretaapian Nasional (RIPNas) 2030, so existing track’s conditions need to be estimated in 2030. On the evaluation, reliability rated by accuracy of travel duration, arrival and departure time. On availability rated by lane capacity using Scott method, and conformity of its lane carrying capacity. On maintainability and safety rated by Track Quality Index (TQI). Then, predicted number of trains pass and planned scenario analysis for 2030. Based on reliability criteria, 97% included on tolerance travel duration, but delays on arrivals and departures more than 40%. Based on availability criteria, lane capacity sufficient up to 515 trains per day, and lane carrying capacity reaches 18,171,648 tons per year. Maintenance and safety criteria based on TQI on the upstream lane of 75% is on very good condition and 61% on downstream lane is in good condition. Based on RIPNas in 2030 there will be 289 trains pass everyday, so the existing railway track is not capable to serve properly and the scenarios are increase the maximum speed to 120 km/hour and add eight block.